Fimbristylis jaleeliana, a new species of Cyperaceae from Kerala, India - Narayanan, Matalayi Kokaramath Ratheesh; Sunil, Chandrasseril Narayanan; Thankappan, Shaju; Sanilkumar, Malayil Gopalan; Rijuraj, Manoharakumar Prasannakumari; Simi, Mattappilly Sugathan (Phytotaxa, 2023)
Fimbristylis jaleeliana, a new sedge species belonging to section Fimbristylis from Kerala State of India is described and illustrated with photographs. Description of new species with distribution, ecology and comparison with its allied taxa are provided.